The Effect of Decision-Making Styles on Life Satisfaction of Employees and Investigation of Life Satisfaction in Terms of Some Demographic Variables - Köse, Ertuğrul (Bursa Teknik Üniversitesi, 2021)
The research was conducted to determine whether the decision-making styles have an effect on the life satisfaction of employees and whether life satisfaction differed according to some demographic variables. Two Likert-type measurement tools were used within the scope of the study. These measurement tools were applied to 400 employees working in the factoring sector in Istanbul, 364 of the participants replied the survey and returned, and 12 survey sheets were evaluated invalid because they contained missing data. As a result, statistical analyzes were conducted on the data in 352 survey sheets. As a result of the study, it was determined that decision-making styles other than avoidance decision-making had an effect on the life satisfaction of employees, and that there was a significant relationship between the life satisfaction of employees and demographic characteristics other than gender and age variables and that the mean scores of the groups indicated a significant difference. It has been determined that the life satisfaction average scores of the employees who have managerial status and in the graduate degree of education group are higher than the other groups.

Araştırma karar verme tarzlarının çalışanların yaşam doyumu üzerinde etkisinin olup olmadığı ve yaşam doyumunun bazı demografik değişkenler açısından farklılık gösterip göstermediğinin belirlenmesi amacıyla gerçekleştirilmiştir. Çalışma kapsamında Likert tipi iki ölçüm aracından yararlanılmıştır. Söz konusu ölçüm araçları İstanbul’da faktoring sektöründe çalışan 400 iş görene uygulanmış, katılımcılardan 364’ü anketi yanıtlayarak geri dönüş yapmış, 12 anket formu ise eksik veri içerdiğinden geçersiz olarak değerlendirilmiştir. Sonuç olarak, istatistikî analizler 352 anket formundaki veriler üzerinden gerçekleştirilmiştir. Araştırma sonucunda karar vermekten kaçınma dışındaki karar verme tarzlarının çalışanların yaşam doyumu üzerinde etkide bulunduğu ve çalışanların yaşam doyumu ile cinsiyet ve yaş değişkeni dışındaki demografik değişkenler arasında anlamlı bir ilişki olduğu ve grupların ortalama puanlarının anlamlı bir farklılık gösterdiği belirlenmiştir. Yönetici unvanına sahip ve lisansüstü öğrenim düzeyi grubunda yer alan çalışanların yaşam doyumu ortalama puanlarının diğer gruplardan daha yüksek olduğu belirlenmiştir.
KARAR VERME TARZLARININ ÇALIŞANLARIN YAŞAM DOYUMU ÜZERİNDEKİ ETKİSİ VE YAŞAM DOYUMUNUN BAZI DEMOGRAFİK DEĞİŞKENLER AÇISINDAN İNCELENMESİ
Keywords: Business Administration; İşletme